2022
DOI: 10.3390/cells11193112
|View full text |Cite
|
Sign up to set email alerts
|

The Tryptophan Catabolite or Kynurenine Pathway in a Major Depressive Episode with Melancholia, Psychotic Features and Suicidal Behaviors: A Systematic Review and Meta-Analysis

Abstract: Major depressive disorder (MDD) and bipolar disorder (BD) with melancholia and psychotic features and suicidal behaviors are accompanied by activated immune-inflammatory and oxidative pathways, which may stimulate indoleamine 2,3-dioxygenase (IDO), the first and rate-limiting enzyme of the tryptophan catabolite (TRYCAT) pathway resulting in increased tryptophan degradation and elevated tryptophan catabolites (TRYCTAs). The purpose of the current study is to systematically review and meta-analyze levels of TRP,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 114 publications
(142 reference statements)
0
17
0
Order By: Relevance
“…In recent meta-analyses, no notable changes in TRYCAT production have been observed in depression and schizophrenia, even though low tryptophan levels are a characteristic of both diseases (Almulla, Thipakorn et al 2022. Increased production of TRYCATs appears to be a characteristic of acute inflammatory conditions, such as critical acute COVID-19 infection (Almulla, Al-Hakeim et al 2023) and interferon-induced depression (Bonaccorso, Marino et al 2002), as opposed to mild chronic inflammatory conditions, such as depression, schizophrenia, and Alzheimer's disease , Almulla, Thipakorn et al 2022.…”
Section: The Trycat Pathway and Long Covidmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent meta-analyses, no notable changes in TRYCAT production have been observed in depression and schizophrenia, even though low tryptophan levels are a characteristic of both diseases (Almulla, Thipakorn et al 2022. Increased production of TRYCATs appears to be a characteristic of acute inflammatory conditions, such as critical acute COVID-19 infection (Almulla, Al-Hakeim et al 2023) and interferon-induced depression (Bonaccorso, Marino et al 2002), as opposed to mild chronic inflammatory conditions, such as depression, schizophrenia, and Alzheimer's disease , Almulla, Thipakorn et al 2022.…”
Section: The Trycat Pathway and Long Covidmentioning
confidence: 99%
“…The copyright holder for this this version posted March 16, 2023. ; https://doi.org/10. 1101/2023.03.11.23287152 doi: medRxiv preprint oxidative stress toxicity (OSTOX) and decreased antioxidant defenses (ANTIOX) , Maes, Rachayon et al 2022 According to a recent meta-analysis, the acute infectious phase is characterized by a considerable activation of indoleamine-2,3-dioxygenase (IDO), which leads to tryptophan depletion and an increase in the synthesis of tryptophan catabolites (TRYCATs) (Almulla, Thipakorn et al 2022). Moreover, activation of the TRYCAT pathway is related to critical illness and higher mortality .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent large-scale meta-analyses by Almulla et al have provided evidence that infection-induced depression can be a distinct type of depression based on its pathomechanism [ 14 , 15 ]. The first analysis showed that patients with MDD and BP were connected, with a decrease in TRP concentration without overactivity of the kynurenine pathway [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pierrucci-Lagha et al found that, in a non-Hispanic Caucasian sample, L A /L A homozygotes showed greater depressive symptoms, whereas among a Hispanic sample, the S/S, L G /L G , and S/L G groups reported the highest rates of depression symptoms during IFN treatment. Analysis of the above-mentioned studies leads to an interesting observation: in studies that simultaneously investigated the impact of HTR1A and 5-HTTLPR polymorphisms on depressive symptoms, only HTR1A significantly influenced the increase in depressive symptoms or the diagnosis of depression [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%